2014
DOI: 10.1038/srep06357
|View full text |Cite
|
Sign up to set email alerts
|

Rectifying Properties of Oligo(Phenylene Ethynylene) Heterometallic Molecular Junctions: Molecular Length and Side Group Effects

Abstract: The rectifying properties of α,ω-dithiol terminated oligo(phenylene ethynylene) molecules sandwiched between heterometallic electrodes, including the molecular length and side group effects, are theoretically investigated using the fully self-consistent nonequilibrium Green's function method combined with density functional theory. The results show nonlinear variation with changes in molecule length: when the molecule becomes longer, the current decreases at first and then increases while the rectification shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It is appreciated that some theoretical groups have successfully studied the length dependence of molecular conductance and given valuable explanation 23 34 35 36 37 38 . On the base of the studies, we find that the exponential decaying character of length dependence seems still having some difficulties to be simulated theoretically when the same series molecular chains are studied 39 , sometimes even the opposite results to the experiments are given 40 . Additionally, in theoretical studies, the interface configurations perform more influence on the electronic transport properties of molecular junctions than in experimental ones 41 42 43 .…”
mentioning
confidence: 91%
“…It is appreciated that some theoretical groups have successfully studied the length dependence of molecular conductance and given valuable explanation 23 34 35 36 37 38 . On the base of the studies, we find that the exponential decaying character of length dependence seems still having some difficulties to be simulated theoretically when the same series molecular chains are studied 39 , sometimes even the opposite results to the experiments are given 40 . Additionally, in theoretical studies, the interface configurations perform more influence on the electronic transport properties of molecular junctions than in experimental ones 41 42 43 .…”
mentioning
confidence: 91%
“…Theoretical and experimental work has revealed that the electron transport properties of molecular junctions can be influenced by either internal or external elements. It is demonstrated that tunneling distance [14][15][16], molecular conformation [17][18][19], contact configuration [20,21], coupling energy [22,23], HOMO-LUMO gap [9,24], and spatial distribution of orbitals [25][26][27] could effectively affect electron transport of molecular junctions. Meanwhile, some external modulations, such as protonation, light, external forces, also have been proved to be efficient methods to control the electron transport properties [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, at negative (positive) voltage, the energy level of the chain elevates (lowers) with the chemical potential of the right electrode, leading to the increase (decrease) of the orbitals scales contributing to transport. Consequently, the rectifying occurs and R > 1 . This conclusion will be further explained by the energy evolution of MPSH states in the subsequent section.…”
Section: Resultsmentioning
confidence: 62%
“…In a word, the degree of the localization and the asymmetry of the MPSH states strengthens with the length increase, resulting in the lower current and higher rectification under the same bias. Combined with the analysis of coupling strength shown in Figure , we conclude that the current variation between the chains might be derived from the change of the eigenstates of the chain and the chain-electrode coupling caused by different chain lengths …”
Section: Resultsmentioning
confidence: 67%